JAK/STAT3 pathway inhibition blocks skeletal muscle wasting downstream of IL-6 and in experimental cancer cachexia - Bonetto, Andrea; Aydogdu, Tufan; Jin, Xiaoling; Zhang, Zongxiu; Zhan, Rui; Puzis, Leopold; Koniaris, Leonidas G; Zimmers, Teresa A (American journal of physiology: endocrinology and metabolism, 2012)
Cachexia, the metabolic dysregulation leading to sustained loss of muscle and adipose tissue, is a devastating complication of cancer and other chronic diseases. Interleukin-6 and related cytokines are associated with muscle wasting in clinical and experimental cachexia, although the mechanisms by which they might induce muscle wasting are unknown. One pathway activated strongly by IL-6 family ligands is the JAK/STAT3 pathway, the function of which has not been evaluated in regulation of skeletal muscle mass. Recently, we showed that skeletal muscle STAT3 phosphorylation, nuclear localization, and target gene expression are activated in C26 cancer cachexia, a model with high IL-6 family ligands. Here, we report that STAT3 activation is a common feature of muscle wasting, activated in muscle by IL-6 in vivo and in vitro and by different types of cancer and sterile sepsis. Moreover, STAT3 activation proved both necessary and sufficient for muscle wasting. In C(2)C(12) myotubes and in mouse muscle, mutant constitutively activated STAT3-induced muscle fiber atrophy and exacerbated wasting in cachexia. Conversely, inhibiting STAT3 pharmacologically with JAK or STAT3 inhibitors or genetically with dominant negative STAT3 and short hairpin STAT3 reduced muscle atrophy downstream of IL-6 or cancer. These results indicate that STAT3 is a primary mediator of muscle wasting in cancer cachexia and other conditions of high IL-6 family signaling. Thus STAT3 could represent a novel therapeutic target for the preservation of skeletal muscle in cachexia.